Best Paper Selection (Yearbook of Medical Informatics, 2021)
Adler-Milstein J, Zhao W, Willard-Grace R, Knox M, Grumbach K. Electronic health records and burnout: Time spent on the electronic health record after hours and message volume associated with exhaustion but not with cynicism among primary care clinicians. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7647261/Brewer LC, Fortuna KL, Jones C, Walker R, Hayes SN, Patten CA, Cooper LA. Back to the Future: Achieving Health Equity Through Health Informatics and Digital Health. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6996775/Reading Turchioe M, Grossman LV, Myers AC, Baik D, Goyal P, Masterson Creber RM. Visual analogies, not graphs, increase patients' comprehension of changes in their health status. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7309237Tschandl P, Rinner C, Apalla Z, Argenziano G, Codella N, Halpern A, Janda M, Lallas A, Longo C, Josep Malvehy J, Paoli J, Puig S, Rosendahl C, Soyer HP, Zalaudek I, Kittler H. Human-computer collaboration for skin cancer recognition. https://www.nature.com/articles/s41591-020-0942-0